Tetrodotoxin: History, Biology, and Synthesis - Makarova, Mariia; Rycek, Lukas; Hajicek, Josef; Baidilov, Daler; Hudlicky, Tomas (Angewandte Chemie (International ed. in English), 2019)
This review provides a comprehensive coverage of the history, biology and chemistry of tetrodotoxin (TTX). It traces the origin of this remarkable molecule all the way back to the ancient Chinese medicine records. The discovery of biological activity, isolation, and a brief overview of structure elucidation are summarized. Next, the biology of TTX is discussed, primarily in the context of its activity in the sodium channels, its anesthetic properties, and its potential use in cancer treatment or drug addiction. Biosynthesis of TTX is covered before the discussion of the total syntheses. All total, formal or partial syntheses are covered but those total syntheses that have been discussed in previous reviews are only briefly summarized. Finally, the synthesis of natural and unnatural derivatives is surveyed, and a conclusion and outlook are provided for this very extensive field of endeavor. To the best of our knowledge the literature coverage is complete up to December 2018.
Keywords: biological activity; lidé; natural products; biosynthesis; total synthesis; Tetrodotoxin; tetrodotoxin; Humans